Graphene Oxide as Proficient Adsorbent for the Removal of Harmful Pesticides: Comprehensive Experimental Cum DFT Investigations. Issue 3 (4th May 2019) - Yadav, Sarita; Goel, Neetu; Kumar, Vinod; Singhal, Sonal
Abstract: Application of graphene oxide (GO) as an adsorbent for the removal of toxic organophosphorus pesticides (OPP's) from aqueous phase has been elucidated by employing both adsorption experiments and first principles calculations based on density functional theory (DFT). Modified Hummer's method was used to synthesize GO followed by its characterization using Fourier transform infrared (FTIR) spectroscopy, powder X-ray diffraction (XRD), field emission scanning electron microscope (FE-SEM) and high-resolution transmission electron microscopy (HR-TEM). Impact of various experimental factors such as adsorbent dosage, pH, pesticide concentration and time on the adsorption efficiency of GO, were studied using adsorption experiments. Equilibrium data were best fitted to Langmuir isotherm model compared to Freundlich isotherm model. Experimental data best fit the Pseudo-second-order model shows the best fit compared to pseudo-first-order, intrapartical diffusion and fractional kinetic adsorption model. In addition to this, feasibility of adsorption process has been understood by performing DFT calculations at B3LYP/6-31G (d) level of theory in the aqueous phase.